Learning Strategies in Developing Entrepreneurial Intention Among Students : Theory of Planned Behavior Approach - Muhammad Nur Afiat; Syamsu Rijal; Dian Safitri Pantja Koesoemasari; Andi Chairil Furqan; Muhammad Ikbal Abdullah (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This research aims to analyze the influence of personal attitude, subjective norm, and perceived behavioral control on entrepreneurial intention of students in the context of learning strategies. The research used a survey method, where questionnaires were distributed to 501 students from several universities using Google Forms. The collected data was analyzed using Structural Equation Modeling - Partial Least Square (SEM-PLS). The results of this study indicate that attitude toward behavior, perceived behavioral control, and subjective norms are important factors that influence entrepreneurial intention in the context of learning strategies. A positive attitude towards behavior increases perceived behavioral control, and a supportive subjective norm can lead to a greater intention to start and manage a business. Although communication may not directly affect behavior, it can indirectly influence behavior through perceived behavioral control and entrepreneurial intention. It is important to consider a range of factors that may impact behavior and design learning strategies that comprehensively address these factors. The quality and nature of communication, along with other variables, may also impact its effect on behavior in learning strategies.